Bullous pemphigoid associated with dipeptidyl peptidase IV inhibitors. A case report and review of literature. - Attaway, Amy (Specjalisci Dermatolodzy, 2014)
BACKGROUND: Bullous pemphigoid is a cutaneous autoimmune blistering disorder. The etiology for what precipitates this disease is not entirely clear at this point, although it has been associated with certain medications. MAIN OBSERVATION: We describe the case of a 70-year-old male with a past medical history of diabetes type 2 who developed a diffuse eruption of bullae with skin biopsy positive for bullous pemphigoid. He had previously been prescribed sitagliptin 50 mg daily for at least one year prior to onset of his disease. The medication was discontinued and the patient was treated with first IV and then oral steroids with good clinical outcome. There have been a few reports that have explored the relationship between DPP-IV inhibitors (gliptins) and bullous pemphigoid, including three case series and a report on sitagliptin associated allergic skin reactions submitted to the Adverse Event Reports System database of the FDA. According to the Naranjo ADR probability score there is a "possible" cause and effect relationship for this case. CONCLUSION: The enzyme DPP-IV is ubiquitously expressed in almost every organ system, including the skin. The exact mechanism at this time is unknown but is believed to be multifactorial involving many aspects of the immune system. Our case and the findings from our literature review further demonstrate a link between dipeptidyl peptidase-IV inhibitors and the development of bullous pemphigoid.